The Effect of Ear and Body Acupuncture Therapy on Reducing Waist Circumference and Body Mass Index in Overweight Cases at Rinjani Sragen Gymnastics Studio - Birawa, Astatin Sisillia Putri; Badri, Sholichan; Putri, Kurnia Eka; Haryanto, Joko Tri (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
The incidence of overweight in adults is increasing over time. Being overweight is a body condition that results in excessive fat mass. Overweight is caused by many factors, including age, physical activity, gender, hormones, genetics, and environment. Acupuncture therapy can be used as a support for weight loss efforts because acupuncture can affect the central nervous system and activate specific areas in the brain. This study aims to determine the effect of ear and body acupuncture therapy on reducing waist circumference and body mass index in overweight cases at the Rinjani Sragen Gymnastics Studio. This study used a quantitative method of research using a “Quasi-Experimental” research design. The study sample was 45 people who were divided into 3 treatment groups, namely group I ear acupuncture therapy, group II ear and body acupuncture therapy, and group III body acupuncture therapy. The study began in January to March 2025 and was conducted at the Rinjani Sragen Gymnastics Studio. One-way ANOVA test analysis on waist circumference has a significant value of ρ of 0.017 (ρ <0.050) and for body mass index, p=0.004 (ρ <0.050), which means that ear and body acupuncture therapy affects reducing waist circumference and body mass index in overweight cases.